2012
DOI: 10.1093/gbe/evs005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Repeat-Induced Point Mutation in Transposable Elements of Basidiomycete Fungi

Abstract: Transposable elements (TEs) are ubiquitous genomic parasites that have prompted the evolution of genome defense systems that restrict their activity. Repeat-induced point mutation (RIP) is a homology-dependent genome defense that introduces C-to-T transition mutations in duplicated DNA sequences and is thought to control the proliferation of selfish repetitive DNA. Here, we determine the taxonomic distribution of hypermutation patterns indicative of RIP among basidiomycetes. We quantify C-to-T transition mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 52 publications
(63 reference statements)
6
46
2
Order By: Relevance
“…Mated cells of M. lychnidis-dioicae respond to corn oil, in addition to the other lipids previously reported [45]. This supports the hypothesis that lipid response may be important for the development of this species.…”
Section: Resultssupporting
confidence: 88%
“…Mated cells of M. lychnidis-dioicae respond to corn oil, in addition to the other lipids previously reported [45]. This supports the hypothesis that lipid response may be important for the development of this species.…”
Section: Resultssupporting
confidence: 88%
“…However, this was not easily corroborated when analyzing a potential genome-wide reduction in CpG dinucleotides (see Supplemental Figure 7 online). The low abundance of repeats could compromise a proper analysis in this fungus; it was concluded previously that S. reilianum and U. maydis likely do not possess a RIP mechanism (Horns et al, 2012). In contrast with U. hordei, U. maydis lacks RNAi, HP1-like, and putative DNA methyltransferase genes, and no RIP mutation mechanism has been identified thus far.…”
Section: Genome Defenses Related To Te Control and Heterochromatin Fomentioning
confidence: 96%
“…2-8). Eighty per cent of TE copies with high frequencies of cytosine mutation showed a bias toward CpG dinucleotides, consistent with the "CpG effects" (Walser & Furano, 2010) of maintenance methylation known in eukaryotes (Fryxell & Moon, 2005;Jiang & Zhao, 2006;Morton et al, 2006), including fungi Horns et al, 2012) where CpG methylation of TEs have been shown in ascomycete and basidiomycete fungi (Zemach et al, 2010). Notably, the rate of CpG mutations varied according to TE order and superfamily examined: TE copies exhibiting a pattern of frequent transition at CpG sites appeared lower for class II DNA transposons (Helitron-type and TIR elements) than that of class I Retrotransposons (21% and 58% respectively) ( Fig.…”
Section: -4)supporting
confidence: 73%
“…SSPs were indeed located nearer to TEs than the set of all other non-SSP genes (Chi-squared p-value < 5e-4; Fig. 2 Hypermutation in TEs that resembles the genome defense, Repeat-Induced Point mutation (RIP), has previously been observed in the LTR elements (copia-like and gypsylike elements) and Helitron transposons of M. lychnidis-dioicae Horns et al, 2012). Some genes that appeared similar to those necessary for RIP in Neurospora crassa (Cambareri et al, 1989;Selker et al, 1987) were found in the M. lychnidis-dioicae genome.…”
Section: -4)mentioning
confidence: 89%